(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the economic efficiency of introducing science, research-based engineering solutions and innovation into the construction sector of Uzbekistan, with particular attention to state support mechanisms, institutional reforms, digitalization, energy efficiency, regulatory modernization and public-private interaction. The relevance of the topic is determined by the rapid growth of construction activity in Uzbekistan, the expansion of housing and infrastructure projects, the rising demand for safe and energy-efficient buildings, and the need to transform construction from a labor- and material-intensive sector into a technologically advanced branch of the national economy. In 2024, the volume of completed construction works in Uzbekistan reached 233.8 trillion soums and increased by 8.8% compared with the previous year; the number of enterprises and organizations engaged in construction activities reached 27,408 units as of January 1, 2025. These figures show that the sector is economically large, socially sensitive and institutionally complex; therefore, even a small improvement in productivity, design accuracy, material efficiency, energy consumption or project management can generate significant macroeconomic effects. The article argues that scientific and innovative development in construction should not be understood only as the use of modern equipment or digital software, but as a full-cycle transformation involving applied construction science, building materials research, seismic safety, BIM and digital twins, energy-efficient design, transparent permitting systems, public procurement, quality control, standardization, professional training and commercialization of research results. The methodological basis of the article is formed by system analysis, economic efficiency assessment, comparative institutional analysis and evaluation of state support mechanisms. The results show that the introduction of science and innovation into construction can reduce life-cycle costs, increase labor productivity, decrease project delays, improve safety, lower energy consumption, raise the quality of urban planning decisions and strengthen the competitiveness of domestic construction companies. At the same time, the article stresses a hard but necessary point: innovation in construction will not produce economic efficiency if it remains at the level of declarations, pilot projects or isolated digital platforms. Its real effect appears only when scientific results are translated into design standards, cost-estimate methods, building codes, procurement requirements, training programs, energy audits and measurable performance indicators.